KAJIAN STILISTIKA DALAM NOVEL METAFORA SUNYI KARYA HERI SAMTANI SERTA RELEVANSINYA SEBAGAI MATERI PEMBELAJARAN SASTRA DI SMA - Mega Rizki Annisa; Dewi Herlina Sugiarti; Uah Maspuroh (Bahtera Indonesia, 2022)
This study aims to describe: (1) diction and language style in the novel Metafora Sunyi by Heri Samtani (pen name Heri ST); (2) the relevance of Heri ST's novel Metafora Sunyi as literature learning material in high school. The research method uses qualitative, with a stylistic approach. The object of research is diction and language style used by Heri ST in the novel Metafora Sunyi. The data collection technique used is the note-taking technique, by reading and understanding the novel and then recording sentences containing the author's distinctive diction and style. The data analysis technique used is content analysis, the researcher analyzes the content of the text after the data is collected. The results showed: (a) diction in the form of connotative words, concrete words, loan words, foreign words, typical greeting words or personal names, and words with objects of natural reality; (b) language style includes: (1) comparative language style in the form of simile or parable, metaphor, personification, depersonification, allegory, antithesis, pleonasm, periphrasis, correction; (2) contradictory language style in the form of hyperbole, (3) linking language style in the form of metonymy, allusion, antonomasia, erothesis, polysyndeton, and (4) repetition language style in the form of anaphora, mesodilopsis, and epanalepsis; (c) The novel Metafora Sunyi by Heri ST can be used as a literature learning material in SMA in KD 3.9 to analyze the content and language in the novel for class XII.